2021
DOI: 10.1021/acs.est.0c07206
|View full text |Cite
|
Sign up to set email alerts
|

Rice Rhizospheric Effects on the Bioavailability of Toxic Trace Elements during Land Application of Biochar

Abstract: Land application of biochar, the product of organic waste carbonization, can improve soil fertility as well as sequester carbon to mitigate climate change. In addition, biochar can greatly influence the bioavailability of toxic trace elements (TTEs) in soils resulting from its large internal surface areas, abundance in organic carbon, and ability to modify soil pH. Most research to date employs batch leaching tests to predict how biochar addition impacts TTE bioavailability, but these ex situ tests rarely cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 67 publications
0
2
1
Order By: Relevance
“…4a and b). In contrast to previous findings (Fang et al 2021b;Yin et al 2020;Williams et al 2014), no apical Fe flux hotspots were observed in our study (Fig. 3).…”
Section: Distribution Of and Relationships Between Labile P Fe S And ...contrasting
confidence: 99%
“…4a and b). In contrast to previous findings (Fang et al 2021b;Yin et al 2020;Williams et al 2014), no apical Fe flux hotspots were observed in our study (Fig. 3).…”
Section: Distribution Of and Relationships Between Labile P Fe S And ...contrasting
confidence: 99%
“…Many scholars have carried out in-depth studies of rhizospheric microflora in model plants and crops such as Arabidopsis thaliana (Bressan et al 2009), corn (Jin et al 2013), and rice (Fang et al 2021) and found that substances secreted by plants can drive and shape different rhizospheric microbial processes. In other words, rhizosphere microorganisms mainly attract specific microbial populations through rhizosphere exudates.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that DOC is an important factor controlling the soil As release and dissolved organic matter will favor the As mobilization through the J o u r n a l P r e -p r o o f formation of dissolved As-Fe-NOM collids/complexes and the reduction of As V to As III under the strongly reducing condition stimulated by exogenous organic matter (Fang et al, 2021). Also, the dissolved organic matter will compete with As for adsorption sites on soil reactive surfaces.…”
Section: Relationship Between Doc and As Dissolutionmentioning
confidence: 99%